Location of Decision Rights Within Multinational Firms - ROBINSON, LESLIE A.; STOCKEN, PHILLIP C. (Journal of Accounting Research, 2013)
ABSTRACT Using U.S.‐based multinational firm data gathered over more than two decades, we examine factors associated with the location of decision rights within these firms, whether the inappropriate assignment of decision rights is associated with poor firm performance, and whether these firms relocate decision rights in response to their evolving environments. We find that a mismatch between the location of decision rights and a firm's environment is associated with weak firm performance. We also show that the likelihood a parent company will alter the assignment of decision rights to a subsidiary is increasing in the extent of a mismatch although this likelihood is decreasing in the strength of the subsidiary's performance.